Self-harm in adolescents: self-report survey in schools in Scotland. - O'Connor, R; Rasmussen, S; Miles, J; Hawton, K (2009)
BACKGROUND: The suicide rate in Scotland is twice as high as that in England. However, the prevalence of self-harm is unknown. AIMS: To determine the prevalence of self-harm in adolescents in Scotland and the factors associated with it. METHOD: A total of 2008 pupils aged 15-16 years completed an anonymous lifestyle and coping survey. Information was obtained on demographic characteristics, lifestyle, life events and problems, social influences, psychological variables and self-harm. RESULTS: Self-harm was reported by 13.8% of the respondents. The majority (71%) of those who had self-harmed had done so in the past 12 months and girls were approximately 3.4 times more likely to report self-harm than boys. In multivariate analyses, smoking, bullying, worries about sexual orientation, self-harm by family and anxiety were associated with self-harm in both genders. In addition, drug use, physical abuse, serious boy/girlfriend problems, self-harm by friends and low levels of optimism were also associated with self-harm in girls. CONCLUSIONS: Despite markedly different national suicide rates, the prevalence of self-harm in Scotland is similar to that in England with girls at least three times more likely to report self-harm than boys. The findings suggest a role for emotional literacy programmes in schools and highlight the importance of promoting positive mental health among adolescents.